Zum Schicksal der Güter der geistlichen Ritterorden in Böhmen und Mähren nach den Hussitenkriegen - Jan, Libor (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2017)
On the fate of the estates of the chivalric orders – Bohemia and Moravia after the Hussite wars The paper deals synoptically with the fate of the estates of the of the Order of the Teutonic Knights and the Order of Saint John at the time of the Hussite wars and the time, which immediately followed. Already in the first decades of the 15th century, the Order of Teutonic Knights had to pledge their commanderies of Miletín and Býčkovice to be able to pay the royal excise tax (berna specialis). However, the real blow for the order estates was the intervention of King Wenceslas IV in 1411. After the Battle of Grunwald, the order owed the king a relatively high sum and attempted to acquire another loan from him, but Wenceslas IV rejected that and on the contrary had important commanderies seized. The author monitors primarily the fates of Chomutov and Drobovice in Bohemia and Slavkov in Moravia. Only in the case of Chomutov at the end of the 15th century did its new holder Beneš of Veitmile provide a certain compensation to the Order of the Teutonic Knights; in the other cases the properties were sequestered without compensation. Also the Order of St John pledges some estates in the pre-Hussite period to acquire money for excise taxes (villages near Ústí nad Labem and Uhříněves). At the beginning of the battles with the Hussites, the Order of St John’s estates were pledged by King Sigismund of Luxembourg. It was for example the relatively large order estate with its centre in Český Dub in North Bohemia or some villages of the Prague convent near castle Panna. Moravian estates were also pledged, for instance Orlovice, Mutěnice and Horní Kounice show the approach of the order, which tried to redeem the estates from pledges; although if it managed in some cases, it pledged them further itself. Despite that, the Order of St John managed to maintain an important order estate with its main residence in Strakonice in South Bohemia, which became a significant anti-Hussite centre. Although the Hussites destroyed many estates, the real liquidators of the order economic bases were Kings Wenceslas IV and Sigismund.